2021
DOI: 10.1002/pca.3040
|View full text |Cite
|
Sign up to set email alerts
|

A supercritical fluid workflow for the quality assessment of herbal drugs and commercial preparations from Rhodiola rosea

Abstract: Introduction Preparations from the Rhodiola rosea are experiencing an increase in popularity: extracts of dried roots and rhizomes are used as adaptogen to treat stress, fatigue, and weakness. To meet high pharmaceutical standards, fast and reliable methods to assess phytochemical variations in respect of quality control are needed. Objective The aim of this study was to extract and quantify seven characteristic secondary metabolites of R. rosea, namely p‐tyrosol (1), rosin (2), rosiridin (3), salidroside (4),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Of the included studies, only two independently tested the RR extract to ensure that the supplement was of the correct concentration (Jówko et al, 2018; Walker et al, 2007). This raises the possibility that not all of the studies were using a RR extract that corresponded to the claimed concentrations, since it has been shown that several commercial RR products failed to meet their claimed extract concentrations of marker compounds (Langeder & Grienke, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Of the included studies, only two independently tested the RR extract to ensure that the supplement was of the correct concentration (Jówko et al, 2018; Walker et al, 2007). This raises the possibility that not all of the studies were using a RR extract that corresponded to the claimed concentrations, since it has been shown that several commercial RR products failed to meet their claimed extract concentrations of marker compounds (Langeder & Grienke, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of extract optimization, only one parameter was changed for each extract to understand the effects of each setting. Several published studies report the successful usage of polar solvents in sub/supercritical fluid chromatography for natural products. …”
Section: Methodsmentioning
confidence: 99%
“…A reduced environmental impact due to shortened run times and the omission of organic solvents as mobile phase, is an additional benefit. Today, SFC and the advanced ultra-high performance SFC (UHPSFC) constitute a versatile technology providing high separation efficiency, access to a broad range of compound classes, with various stationary phase chemistries available and high compatibility with numerous detectors ( Schretter et al, 2020 ; Ganzera and Zwerger, 2021 ; Langeder and Grienke, 2021 ). For these reasons, this first UHPSFC method for the quantitative analysis of DRAs is preferable to the previously suggested techniques.…”
Section: Introductionmentioning
confidence: 99%